TINGKAT PARTISIPASI ANGGOTA KOPERASI UNIT DESA MILIK BERSAMA DI DESA BUKIT LINGKAR KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Yulida, Roza; ', Jadmiko; ', Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research was to know the degree participant of members Milik Bersama cooperation in Bukit Lingkar, Batang Cenaku in indragiri hulu regency. This research used survey method. The total of sample this research was 42 people who gain by using formula slovin. This research was using random sampling. The sample found randomly from 889 members Milik Bersama cooperation. The collecting data of this research was using primary data and secondary data. To analyze the degree and the problems at participation of this research was using descriptive method. To obtain the degree of participation of getting result at meeting, implementation of participant in cooperation activities, participant to gain the function of service, and evaluation of programs cooperation. The degree of members participation measured by using quesioner of Likert Scale. The degree participant of members Milik Bersama cooperation in Bukit Lingkar, Batang Cenaku, Indragiri Hulu Regency was high with score 3,64. High of the degree participant on members Milik Bersama Cooperation support by high participant members on meeting, implementation, service, also evaluation programs of cooperation. In another side, the programs Milik Bersama Cooperation in Bukit Lingkar, Batang Cenaku, Indragiri Hulu Regency had some problems that related by the degree of participant were pasif on cooperation activities, attendance, lack gave ideas on meeting, less armada dum truck, and participant on activity and evaluation of programs Milik Bersama Cooperation. Key Words: The Degree of Participant, Cooperation, KUD Milik Bersama.